APLIKASI PEMBELAJARAN MATEMATIKA DASAR UNTUK ANAK-ANAK BERBASIS ANDROID - Ari Indra Indra Widyawan; Hery Oktafiandi (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
Currently smartphone technology has grown rapidly with various operating systems such as Ios, Windows Phone and Android. One thing that attracted many people today is Android. Education has also used the software to create interactive learning applications. Media learning of mathematics is now available in several forms, including in the form of books and e-learning. This book has its limitations can only display information in the form of text and pictures, easily destroyed by water, and make it difficult to carry anywhere as it requires a large storage space. While mobile phones with android operating system can be used as a solution of the present study can be taken anywhere. Mathematics is one of the compulsory subjects to be studied, because mathematics is a prerequisite for learning math. To follow the development of the necessary methods and practical mobile learning, but can meet learning needs. Then make an application for Mobile as a medium of learning mathematics. The author hopes that this application can make hopefully with increased interest in learning mathematics, as well as make it easier for anyone who wants to learn math. The application of mathematics teaching and quizzes can be used as an alternative to learning mathematics that can display text, images and sound. Its use is more effective, more efficient, and can be accessed anywhere. Keywords : Android, Mathematics, Learning, Mobile Application